2015
DOI: 10.1159/000443943
|View full text |Cite
|
Sign up to set email alerts
|

Male Sexual Development and the Androgenic Gland: Novel Insights through the de novo Assembled Transcriptome of the Eastern Spiny Lobster,<b><i> Sagmariasus verreauxi</i></b>

Abstract: The Eastern spiny lobster, Sagmariasus verreauxi, is commercially important in fisheries, with growing aquaculture potential, driving an interest to better understand male sexual differentiation. Amongst the Decapoda, the androgenic gland (AG) and the insulin-like androgenic gland hormone (IAG) have a well-defined function in male sexual differentiation. However, IAG is not a sex determinant and therefore must be considered as part of a broader, integrated pathway. This work uses a transcriptomic, multi-tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 81 publications
3
32
0
Order By: Relevance
“…The lengthy transition, the large-sized larvae and their transparency enable clear molt staging by gut retraction. The availability of transcriptomic data for both the larval metamorphic transition at high resolution [35], alongside tissues of juveniles and adults from this species [44][45][46][47][48][49] enables thorough examination of expression patterns and correlation with spatial-temporal expression.…”
Section: Metamorphosis In Spiny Lobstersmentioning
confidence: 99%
See 3 more Smart Citations
“…The lengthy transition, the large-sized larvae and their transparency enable clear molt staging by gut retraction. The availability of transcriptomic data for both the larval metamorphic transition at high resolution [35], alongside tissues of juveniles and adults from this species [44][45][46][47][48][49] enables thorough examination of expression patterns and correlation with spatial-temporal expression.…”
Section: Metamorphosis In Spiny Lobstersmentioning
confidence: 99%
“…Where ORF was predicted to be partial, iterative tBLASTn searches using CLC Genomics Workbench (Qiagen, version 8.0.3), against the transcriptome of both developmental stages [35] and juvenile and mature tissues [44,48], were performed in order to identify flanking regions. The predicted ORFs were searched for CYP450 domains using PFAM database in CLC Genomics Workbench.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The most compelling evidence of a sex pheromone has been demonstrated from research on the blue crab, Callinectes sapidus , where N -acetylglucosamino-1,5-lactone (NAGL) present in the female AnG urine at intermolt and premolt, can activate physiological and behavioural responses in conspecifics [12]. Supporting a key role for the AnG in sex pheromone release, a recent transcriptomic screen of several tissues from the Eastern spiny lobster ( Sagmariasus verreauxi ), found that the most significantly biased transcript expression between males and females is within the AnG (other than the gonad) [13]. However, a large-scale analysis of this gland utilising a combined approach of transcriptomic, proteomic and metabolomic methodologies has not been performed to date.…”
Section: Introductionmentioning
confidence: 99%